A new species of the sandperch genus Parapercis from the Philippines Perciformes: Pinguipedidae) - Ho, Hsuan-Ching; Heden, Miranda Van (Zootaxa, 2017)
A new species sandperch, Parapercis altipinnis, is described based on the holotype collected from Cebu, the Philippines at 55–65 m by SCUBA. The new species belongs to the P. cylindrica complex and can be distinguished by an extremely high first dorsal fin, the first spine slightly longer than the head; 3 predorsal scales; 42 or 43 lateral-line scales; teeth present on vomer and palatines. The body is reddish dorsally and blackish ventrally, with 5 large brownish saddles alternating with white bands on dorsal surface; scattered dots on top of head, first dorsal fin and dorsal surface; first dorsal fin milky white with 5 black marks on anterior margin; a black broad band below eye; cheek and throat blackish red surrounding by white color; row of 10 short white bars along the lateral side of body axis; row of 9 deep red to blackish bars on lower half of lateral side of body; base of pelvic fin and lower margin of caudal fin blackish; rows of black spots on soft dorsal fin. A key to the species of the complex is provided.